A method for synthesizing highly thickening lithium magnesium silicate

By controlling the reaction pressure and co-heating with water, the problems of large particle size and high layer charge in traditional hydrothermal synthesis are solved, and small particle size, low layer charge, high light transmittance and extremely strong increase are achieved. The preparation of thick lithium magnesium silicate simplifies the preparation process and improves the stability and performance of the product.

CN118754145BActive Publication Date: 2024-12-17SHANDONG HAIHUA GRP CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411245215.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-17
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

When preparing lithium magnesium silicate by traditional hydrothermal synthesis, the unstable reaction pressure leads to poor dissolution and mass transfer effects, the product has large particle size and high layer charge, resulting in poor dispersion, low light transmittance and poor thickening.

Method used

Carbon dioxide is used to control the reaction pressure, and together with water, the small particle size and low-layer charge lithium magnesium silicate is prepared through ultrasonic dispersion and appropriate reaction temperature and time.

Benefits of technology

It improves the light transmittance and thickening ability of lithium magnesium silicate, shortens the reaction cycle, ensures that the particle size distribution of the product is narrow, stable in performance, and the raw materials are cheap and easy to obtain, and the preparation process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a synthesis method of a high thickening lithium magnesium silicate, and belongs to the technical field of preparation of silicate materials. It uses sodium silicate, magnesium salt, and lithium salt as raw materials, and water as the main solvent, and reacts in a closed stirring reactor, the reaction temperature is 180-300 ° C, and carbon dioxide is introduced to control the reaction pressure at 2-6MPa. Carbon dioxide in a near-critical state acts as a secondary solvent and water to dissolve, transfer mass, and transfer heat, and reacts for 2-4 hours before separation and drying, and finally obtains lithium magnesium silicate with small particle size and low layer charge. The lithium magnesium silicate has excellent thickening ability, and its aqueous dispersion has extremely high light transmittance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of silicate materials, and in particular to a method for synthesizing high-thickening lithium magnesium silicate. Background Art

[0002] Lithium magnesium silicate, also known as hectorite and hectorite, is a non-toxic, odorless, non-irritating white powder. The natural mineral reserves of lithium magnesium silicate are extremely small, and most of them are obtained through artificial chemical synthesis. Lithium magnesium silicate has a unique lamellar structure and is easy to form gel in water. When mixed with water, the particles will expand rapidly until the flakes separate. Because the flake layers are negatively charged and the end faces are positively charged, the end faces of the separated flakes are attracted to the layers of another flake, thereby quickly forming a three-dimensional colloidal structure, namely a card palace structure, which increases the viscosity of the system. This characteristic makes lithium magnesium silicate an ideal thickening rheological agent for water systems, especially suitable for cosmetics, inks and coatings.

[0003] The main method for synthesizing lithium magnesium silicate is the hydrothermal synthesis method, which uses water as a solvent and prepares the corresponding product in a closed reactor at a certain reaction temperature and time. As the reaction temperature increases, the air pressure in the reactor continues to increase, the density of the water body decreases, resulting in a decrease in surface tension, thereby increasing the ion product of water, resulting in water being able to dissolve, transmit pressure, and promote the reaction in the reactor. The traditional hydrothermal synthesis method usually does not control the reaction pressure, and the pressure changes continuously during the reaction process, resulting in poor dissolution and mass transfer effects of the reaction, which ultimately affects the quality of the product. The traditional hydrothermal method for synthesizing lithium magnesium silicate requires a long reaction time. Due to the poor stability of the reaction, the product has a larger particle size and a higher layer charge. The large particle size of the product leads to poor dispersibility and low transmittance during application, and the higher layer charge leads to an enhanced binding force with impurity cations, which is not easy to peel off to form a card palace structure, thereby making the thickening property worse during application. Summary of the invention

[0004] The purpose of the present invention is to provide a method for synthesizing lithium magnesium silicate with high thickening property. The preparation method provided by the present invention is simple, the raw materials are cheap and readily available, and carbon dioxide is used to increase the dissolution, heat transfer and mass transfer effects of the reaction to obtain lithium magnesium silicate with small particle size and low layer charge, which exhibits high light transmittance and extremely strong thickening ability.

[0005] The technical solution of the present invention is:

[0006] The invention provides a method for synthesizing lithium magnesium silicate with high thickening property, which uses sodium silicate, magnesium salt and lithium salt as raw materials, utilizes carbon dioxide to control the reaction pressure, and carbon dioxide and water jointly play the role of mass transfer and heat transfer to prepare lithium magnesium silicate with high light transmittance and extremely strong thickening ability.

[0007] The preparation method comprises:

[0008] Step 1: Mix sodium silicate, magnesium salt, lithium salt and deionized water, stir evenly, and perform ultrasonic dispersion to obtain dispersion A;

[0009] Step 2: Heat the dispersion A under pressure-controlled carbon dioxide to obtain a suspension B, filter and separate the solid, wash with water, and dry to obtain lithium magnesium silicate.

[0010] Preferably, the mass ratio of the sodium silicate, magnesium salt, lithium salt and deionized water is 35-60: 25-50: 3-8: 150-300. The addition ratio of the raw materials is to control the ratio of silicon, magnesium and lithium in the final structure. The appropriate addition ratio is conducive to the faster and more complete formation of the magnesium lithium silicate structure.

[0011] Preferably, the modulus of the sodium silicate is in the range of 2.6-4.0. The modulus is a basic index of sodium silicate, which represents the molar ratio of silicon dioxide to sodium oxide in the sodium silicate. The sodium silicate solution can be used directly, and the sodium silicate powder can be used after being dissolved.

[0012] The magnesium salt is any one of magnesium chloride, magnesium sulfate or magnesium nitrate;

[0013] The lithium salt is any one of lithium hydroxide, lithium chloride, lithium carbonate or lithium fluoride.

[0014] Preferably, the reaction temperature of the heating reaction is 180-300°C, the reaction time is 2-4h, and the preferred reaction temperature is 220-260°C.

[0015] Preferably, the carbon dioxide controls the reaction pressure in the range of 2-6 MPa.

[0016] Preferably, the drying method is vacuum drying or flash drying, preferably flash drying, and the drying temperature is 100-200° C., preferably 140-160° C. While ensuring that moisture and impurities are completely removed, the drying time should be shortened as much as possible to ensure that the layered structure is not destroyed.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0018] (1) The present invention uses carbon dioxide to assist water in promoting the reaction. Under appropriate reaction pressure and temperature, carbon dioxide is in a near-critical or supercritical state and has a strong solubility. Together with water, it can dissolve, transfer heat, and transfer mass, making the reaction raw materials crystallize faster and with better crystallinity, thereby reducing the particle size of the reaction product and lowering the layer charge, thereby improving the light transmittance and thickening ability of the product.

[0019] (2) The present invention controls the reaction pressure by introducing carbon dioxide. Reducing the pressure fluctuation during the reaction process will enhance the stability and safety of the reaction, improve the reaction uniformity at each position in the reactor, and thus make the particle sizes of the reaction products obtained in the same batch closer, the particle size distribution narrower, and the performance more stable.

[0020] (3) The present invention uses appropriate reaction pressure and temperature to promote the reaction. Reaction temperature and reaction pressure are key factors affecting product quality. Appropriate reaction pressure and temperature promote the role of carbon dioxide, while ensuring a small particle size structure of the product, shortening the reaction cycle and ensuring that the reaction is completed within 2-4 hours.

[0021] (4) The present invention uses high modulus sodium silicate as raw material. Silicon is an important element in the skeleton structure of lithium magnesium silicate. Compared with low modulus sodium silicate, high modulus sodium silicate has fewer impurities and higher silicon content, which is conducive to forming a product with smaller particle size.

[0022] (5) The preparation method provided by the present invention is simple, the raw materials are cheap and easily available, and the reaction cycle is short. While carbon dioxide is used to control the reaction pressure, carbon dioxide and water can jointly play the role of dissolution, heat transfer, and mass transfer. The obtained lithium magnesium silicate has a small particle size and low layer charge. Its aqueous dispersion exhibits a high transmittance of 99.1-99.5%, and the thickening viscosity reaches 2320-2850 cP. DETAILED DESCRIPTION

[0023] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0024] The technical solutions provided by the present invention will be described clearly and completely below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0025] This embodiment provides a method for synthesizing high thickening lithium magnesium silicate, which is as follows:

[0026] 35 g of sodium silicate with a modulus of 3.5, 50 g of magnesium chloride and 3 g of lithium hydroxide were added to 300 g of deionized water in sequence, stirred and mixed evenly, and ultrasonically dispersed to obtain dispersion A; dispersion A was placed in a closed stirring reactor, carbon dioxide was introduced to replace the air in the reactor, the temperature was raised to 220° C., and the carbon dioxide gas source and the reactor were connected at the same time. The pressure reducing valve was adjusted to control the reaction force at 6 MPa. After reacting for 4 hours, the suspension was taken out to obtain suspension B, and the solid separated by washing and filtration was vacuum dried at 100° C. to obtain high thickening lithium magnesium silicate, named S1. Example 2

[0027] This embodiment provides a method for synthesizing high thickening lithium magnesium silicate, which is as follows:

[0028] 38 g of sodium silicate with a modulus of 2.9, 25 g of magnesium sulfate and 4 g of lithium fluoride were added to 150 g of deionized water in sequence, stirred and mixed evenly, and ultrasonically dispersed to obtain dispersion A; dispersion A was placed in a closed stirring reactor, carbon dioxide was introduced to replace the air in the reactor, the temperature was raised to 300°C, and the carbon dioxide gas source and the reactor were connected at the same time, the pressure reducing valve was adjusted to control the reaction force at 5 MPa, and the solid was taken out after reacting for 2 hours, washed with water, filtered and separated, and flash dried at 140°C to obtain high thickening lithium magnesium silicate, named S2. Example 3

[0029] This embodiment provides a method for synthesizing high thickening lithium magnesium silicate, which is as follows:

[0030] 55 g of sodium silicate with a modulus of 3.2, 45 g of magnesium nitrate and 5 g of lithium carbonate were added to 200 g of deionized water in sequence, stirred and mixed evenly, and ultrasonically dispersed to obtain dispersion A; dispersion A was placed in a closed stirring reactor, carbon dioxide was introduced to replace the air in the reactor, the temperature was raised to 180° C., and the carbon dioxide gas source and the reactor were connected at the same time. The pressure reducing valve was adjusted to control the reaction force at 2 MPa. After reacting for 3 hours, the solid was taken out, washed with water, filtered and separated, and flash dried at 160° C. to obtain high-thickening lithium magnesium silicate, named S3. Example 4

[0031] This embodiment provides a method for synthesizing high thickening lithium magnesium silicate, which is as follows:

[0032] 50 g of sodium silicate with a modulus of 2.6, 30 g of magnesium nitrate and 6 g of lithium hydroxide were added to 300 g of deionized water in sequence, stirred and mixed evenly, and ultrasonically dispersed to obtain dispersion A; dispersion A was placed in a closed stirring reactor, carbon dioxide was introduced to replace the air in the reactor, the temperature was raised to 260° C., and the carbon dioxide gas source and the reactor were connected at the same time, and the pressure reducing valve was adjusted to control the reaction force at 4 MPa. After reacting for 2 hours, the solid was taken out, washed with water, filtered and separated, and flash dried at 150° C. to obtain high thickening lithium magnesium silicate, named S4. Example 5

[0033] This embodiment provides a method for synthesizing high thickening lithium magnesium silicate, which is as follows:

[0034] 47 g of sodium silicate with a modulus of 3.8, 38 g of magnesium sulfate and 8 g of lithium carbonate were added to 250 g of deionized water in sequence, stirred and mixed evenly, and ultrasonically dispersed to obtain dispersion A; dispersion A was placed in a closed stirring reactor, carbon dioxide was introduced to replace the air in the reactor, the temperature was raised to 240°C, and the carbon dioxide gas source and the reactor were connected at the same time, and the pressure reducing valve was adjusted to control the reaction force at 3 MPa. After reacting for 4 hours, the solid was taken out, washed with water, filtered and separated, and flash dried at 200°C to obtain high thickening lithium magnesium silicate, named S5. Example 6

[0035] This embodiment provides a method for synthesizing high thickening lithium magnesium silicate, which is as follows:

[0036] 60 g of sodium silicate with a modulus of 4.0, 25 g of magnesium chloride and 8 g of lithium chloride were added to 300 g of deionized water in sequence, stirred and mixed evenly, and ultrasonically dispersed to obtain dispersion A; dispersion A was placed in a closed stirring reactor, carbon dioxide was introduced to replace the air in the reactor, the temperature was raised to 220° C., and the carbon dioxide gas source and the reactor were connected at the same time, and the pressure reducing valve was adjusted to control the reaction force at 4 MPa. After reacting for 3 hours, the solid was taken out, washed with water, filtered and separated, and vacuum dried at 180° C. to obtain high-thickening lithium magnesium silicate, named S6.

[0037] Comparative Example 1

[0038] This comparative example provides a method for synthesizing lithium magnesium silicate, without introducing carbon dioxide and controlling the reaction pressure, and other parameters and steps are the same as those in Example 1, to obtain lithium magnesium silicate, named S7.

[0039] Comparative Example 2

[0040] This comparative example provides a method for synthesizing lithium magnesium silicate, wherein carbon dioxide is introduced but the reaction pressure is not controlled, and other parameters and steps are the same as those in Example 1, to obtain lithium magnesium silicate, which is named S8.

[0041] Comparative Example 3

[0042] This comparative example provides a method for synthesizing lithium magnesium silicate. Carbon dioxide is not introduced, but nitrogen that does not participate in the reaction is introduced to control the reaction pressure. Other parameters and steps are the same as those in Example 1 of this patent, and lithium magnesium silicate is obtained, which is named S9.

[0043] Comparative Example 4

[0044] This comparative example provides a method for synthesizing lithium magnesium silicate. The modulus of the sodium silicate used is 2.0, and the other parameters and steps are the same as those in Example 1 to obtain lithium magnesium silicate, which is named S10.

[0045] Comparative Example 5

[0046] This comparative example provides a method for synthesizing lithium magnesium silicate. The reaction pressure is controlled at 1 MPa. Other parameters and steps are the same as those in Example 1. Lithium magnesium silicate is obtained and is named S11.

[0047] Comparative Example 6

[0048] This comparative example provides a method for synthesizing lithium magnesium silicate. The reaction temperature is controlled at 100° C. Other parameters and steps are the same as those in Example 1. Lithium magnesium silicate is obtained and is named S12.

[0049] Test Example 1

[0050] The average particle size D50 and coarse end particle size D90 of samples S1-S12 were tested by laser particle size analyzer, and the distribution parameter D90 / D50 was calculated and recorded in Table 1; the layer charge§ was calculated by crystal chemical formula method and alkyl quaternary ammonium salt method and recorded in Table 1.

[0051] Test Example 2

[0052] Samples S1-S12 were added to domestic water, and the transmittance of the 1% aqueous dispersion was tested using a transmittance meter, and the results are recorded in Table 1. A rheological test was performed on the 2.5% aqueous dispersion using a rotational rheometer, and the viscosity was recorded after standing for 12 hours and recorded in Table 1.

[0053]

[0054] In general, by comparing samples S7-S12, it can be found that samples S1-S6 of embodiments 1-6 of the present invention have the characteristics of small particle size, low layer charge, high light transmittance, and high thickening viscosity.

[0055] Comparative Example 1 does not introduce carbon dioxide and does not control the pressure. It adopts a typical traditional hydrothermal synthesis method. It can be seen that the particle size of its product S7 is relatively large, and the high value of D90 / D50 means that its particle size distribution is wider, the layer charge is higher, and the transmittance and thickening performance are poor.

[0056] In Comparative Example 2, carbon dioxide is introduced but the pressure is not controlled. Due to the instability of the pressure during the reaction, the effect of carbon dioxide is weakened, and the particle size of the product S8 is smaller than that of the traditional hydrothermal synthesis method, but it is still larger than that of the present invention. Failure to control the pressure leads to a wider distribution of particle sizes, a higher layer charge, and poorer transmittance and thickening properties.

[0057] In Comparative Example 3, nitrogen was introduced to control the reaction pressure. Although there was no reaction-promoting effect of carbon dioxide, the pressure control made the particle size distribution of the product S9 relatively narrow, the particle size was large, the layer charge was high, and the light transmittance and thickening performance were poor. In Comparative Example 4, low-modulus sodium silicate was used, which had low silicon content and many impurities, resulting in the lithium magnesium silicate being easily agglomerated to form large particles, and the impurities increased the layer charge, and the light transmittance and thickening performance were greatly reduced.

[0058] The reaction pressure of Comparative Example 5 is relatively low, resulting in reduced solubilization and mass transfer capabilities of carbon dioxide and water, and the thickening performance of the product S11 is inferior to that of the present invention.

[0059] The reaction temperature of Comparative Example 6 is relatively low, resulting in a significant decrease in the reaction rate. Ultimately, lithium magnesium silicate with a complete structure is not formed, and there is no layer charge.

[0060] In summary, the synthesis method of high thickening lithium magnesium silicate provided by the present invention has the characteristics of simplified and efficient preparation process, cheap and easy-to-obtain raw materials, and short reaction cycle. It utilizes carbon dioxide and water to co-thermally synthesize to obtain lithium magnesium silicate with small particle size and low layer charge, which exhibits high transmittance and extremely strong thickening ability.

[0061] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for synthesizing high thickening lithium magnesium silicate, characterized in that: Step 1: Mix sodium silicate, magnesium salt, lithium salt and deionized water, stir evenly, and perform ultrasonic dispersion to obtain dispersion A; Step 2: heating the dispersion A under controlled pressure by introducing carbon dioxide to obtain a suspension B, filtering and separating the solid, washing with water, and drying to obtain a highly thickening lithium magnesium silicate; In the step 2, the reaction temperature of the heating reaction is 180-300° C., the reaction pressure is controlled at 2-6 MPa, and the reaction time is 2-4 h.

2. The method for synthesizing high thickening lithium magnesium silicate according to claim 1, characterized in that: In step 1, the mass ratio of sodium silicate, magnesium salt, lithium salt and deionized water is 35-60:25-50:3-8:150-300.

3. The method for synthesizing high thickening lithium magnesium silicate according to claim 1, characterized in that: In step 1, the modulus range of sodium silicate is 2.6-4.0; the magnesium salt is any one of magnesium chloride, magnesium sulfate or magnesium nitrate; and the lithium salt is any one of lithium hydroxide, lithium chloride, lithium carbonate or lithium fluoride.

4. The method for synthesizing high thickening lithium magnesium silicate according to claim 1, characterized in that: The drying method is vacuum drying or flash drying, and the drying temperature is 100-200°C.

Citation Information

Cited By

  • Process for preparing a hectorite-type phyllosilicate under supercritical conditions and hectorite-type phyllosilicate obtainable by the process, and use thereof

    WO2026132475A1